Using Acoustic Structure Quantification During B‐Mode Sonography for Evaluation of Hashimoto Thyroiditis. (5th November 2015) - Rhee, Sun Jung; Hong, Hyun Sook; Kim, Chul-Hee; Lee, Eun Hye; Cha, Jang Gyu; Jeong, Sun Hye
Abstract : Objectives: This study aimed to evaluate the usefulness of Acoustic Structure Quantification (ASQ; Toshiba Medical Systems Corporation, Nasushiobara, Japan) values in the diagnosis of Hashimoto thyroiditis using B‐mode sonography and to identify a cutoff ASQ level that differentiates Hashimoto thyroiditis from normal thyroid tissue. Methods: A total of 186 thyroid lobes with Hashimoto thyroiditis and normal thyroid glands underwent sonography with ASQ imaging. The quantitative results were reported in an echo amplitude analysis (Cm 2 ) histogram with average, mode, ratio, standard deviation, blue mode, and blue average values. Receiver operating characteristic curve analysis was performed to assess the diagnostic ability of the ASQ values in differentiating Hashimoto thyroiditis from normal thyroid tissue. Intraclass correlation coefficients of the ASQ values were obtained between 2 observers. Results: Of the 186 thyroid lobes, 103 (55%) had Hashimoto thyroiditis, and 83 (45%) were normal. There was a significant difference between the ASQ values of Hashimoto thyroiditis glands and those of normal glands ( P < .001). The ASQ values in patients with Hashimoto thyroiditis were significantly greater than those in patients with normal thyroid glands. The areas under the receiver operating characteristic curves for the ratio, blue average, average, blue mode, mode, and standard deviation were: 0.936, 0.902, 0.893, 0.855, 0.846, and 0.842, respectively. The ratio cutoff value of 0.27 offered the best diagnostic performance, with sensitivity of 87.38% and specificity of 95.18%. The intraclass correlation coefficients ranged from 0.86 to 0.94, which indicated substantial agreement between the observers. Conclusions: Acoustic Structure Quantification is a useful and promising sonographic method for diagnosing Hashimoto thyroiditis. Not only could it be a helpful tool for quantifying thyroid echogenicity, but it also would be useful for diagnosis of Hashimoto thyroiditis.